2009
DOI: 10.1002/lary.20657
|View full text |Cite
|
Sign up to set email alerts
|

Transoral resection of short segment Zenker's diverticulum and cricopharyngeal myotomy: An alternative minimally invasive approach

Abstract: Objectives/Hypothesis: Transoral treatment of cricopharyngeal bar and small Zenker's diverticulum remains a challenge. We propose a new transoral approach for transoral cricopharyngeal myotomy (TOCPM) for patients with cricopharyngeal spasm and pharyngeal bar, and for transoral resection of diverticula (TORD) with cricopharyngeal myotomy in the patient with small (<3 cm) Zenker's diverticulum.Methods: A retrospective review was conducted of 45 patients with cricopharyngeal spasm (21) and Zenker's diverticulum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The difference in arrival time and sound intensity between the ears (interaural time and level differences) are crucial cues for determining the location of a sound. CI users have limited access to these cues, especially the around 95% 14 of users who are implanted in only one ear 4 , 15 . As a result, CI users have smaller improvements in speech-in-noise performance than normal-hearing listeners when the speech and noise are spatially separated, particularly those that have only one implant 16 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The difference in arrival time and sound intensity between the ears (interaural time and level differences) are crucial cues for determining the location of a sound. CI users have limited access to these cues, especially the around 95% 14 of users who are implanted in only one ear 4 , 15 . As a result, CI users have smaller improvements in speech-in-noise performance than normal-hearing listeners when the speech and noise are spatially separated, particularly those that have only one implant 16 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This experience highlights the risk of an unprotected friable wound in the airway. Fibrin glue (fibrin sealant) is composed of human plasma proteins and mimics the final pathway of the coagulation cascade, yielding a stable and insoluble clot [9]. The role of fibrin sealants throughout surgery is expanding and the use of fibrin has been described to line the repair of cricopharyngeal myotomy and in tracheal lacerations [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin glue (fibrin sealant) is composed of human plasma proteins and mimics the final pathway of the coagulation cascade, yielding a stable and insoluble clot [9]. The role of fibrin sealants throughout surgery is expanding and the use of fibrin has been described to line the repair of cricopharyngeal myotomy and in tracheal lacerations [9, 10]. Our patient suffered no complications associated with the use of fibrin glue and we have demonstrated that Tisseel can be applied to the larynx with the use of jet ventilation provided a pause in ventilation is permitted.…”
Section: Discussionmentioning
confidence: 99%
“…The ECPM is obviously a less invasive technique and requires less operating time than the TCPM 3–5. The mucosa‐covered cricopharyngeal muscle is easily identified as the mound of tissue just proximal to the esophageal introitus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1A)1, 3 and is able to selectively cut off the horizontal part of the cricopharyngeal muscle that is absent of the median pharyngeal raphe 6. The resection of the horizontal part alone will have a sufficient effect for such conditions as Zenker's diverticulum 4. But if a sufficient opening by this part's resection (Fig.…”
Section: Discussionmentioning
confidence: 99%